Efektivitas Progressive Muscle Relaxation dan Mindfulness sebagai Manajemen Nyeri Kepala - Handira Nadhifatul Aini; Jaka Surya Hakim; Natalia Christin Tiara Revita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of Progressive Muscle Relaxation and Mindfulness as mind-body therapy for headache management to children and adults. The method used is a systematic review of articles obtained from databases pubmed, proquest, Google Scholar, and scopus. The results showed that Progressive Muscle Relaxation and Mindfulness with and without combination are effective to reduce headache, improve quality of life, improve sleep quality, and reduce stress level. Conclusion, mind-body therapy such as Progressive Muscle Relaxation and Mindfulness are useful to headache management for all ages. Keywords : Headache Management, Mindfulness, Progressive Muscle Relaxation.